1996
DOI: 10.1111/j.1445-2197.1996.tb00733.x
|View full text |Cite
|
Sign up to set email alerts
|

Australian Multicentre Evaluation of a New Polyurethane Vascular Access Graft

Abstract: Background:A new three-layered cast polyurethane vascular access graft (Thoratec@ VAG) is the most recent addition to the list of materials used in the search for the perfect prosthetic graft material for haemodialysis vascular access. Despite its use in 23 countries, a clinical assessment has not been published. Methods: An independent retrospective evaluation by questionnaire was obtained for 145 implantation procedures performed by 30 surgeons. Results: Ninety-two per cent of procedures were performed for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 13 publications
(1 reference statement)
5
27
2
Order By: Relevance
“…5 These rates are comparable to those of ePTFE grafts at 1 year of 77% (primary) and 64% (secondary). 7,8,[13][14][15] The 3-year primary and secondary patency rates in our study of 55% and 72%, respectively, fall within the standards set by the National Kidney Foundation, 16 which recommends that the cumulative patency rates of all dialysis AV grafts should be at least 70% at 1 year, 60% at 2 years, and 50% at 3 years.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…5 These rates are comparable to those of ePTFE grafts at 1 year of 77% (primary) and 64% (secondary). 7,8,[13][14][15] The 3-year primary and secondary patency rates in our study of 55% and 72%, respectively, fall within the standards set by the National Kidney Foundation, 16 which recommends that the cumulative patency rates of all dialysis AV grafts should be at least 70% at 1 year, 60% at 2 years, and 50% at 3 years.…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, upper arm grafts should pose a lower risk of thrombosis than do forearm grafts as the vessels there are larger with higher flow rates. However, this study as well as others 5,8 did not show any differences in the thrombosis rates in these patient groups.…”
Section: Discussioncontrasting
confidence: 63%
“…According to this study, a problem-free (primary) and functional (secondary) patency was reported in 44.9% and 64.5% of the patients, respectively. It was concluded that PVAG is the graft of choice in patients requiring an urgent, reliable, medium- to long-term hemodialysis access (18). On the contrary, other studies have shown PTFE to be an efficient vascular access for hemodialysis where a primary fistula or brachio-basilic transplantation is not possible (6,17,19).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies in the late 1970s suggested that ePTFE was equal to or better than other available synthetic grafts or biografts in terms of long-term patency and had an acceptable complication rate; hence ePTFE rapidly became the preferred choice of many surgeons as graft material for secondary arteriovenous access in hemodialysis patients. [86][87][88][89][90] Although problems have been reported with some of the polyurethane graft designs, 87,89,90 recent studies have suggested that the polyurethane Vectra graft (Thoratec Lab Corp, CA) is comparable to ePFTE in terms of patency and complications. Both types of ePTFE graft have similar pore size but the Gore-Tex brand is thicker and is reinforced by an external circumferential layer of PTFE not used in Impra grafts.…”
Section: Graft Materialsmentioning
confidence: 99%